Attosecond Time-Resolved Photoelectron Dispersion and Photoemission Time Delays - Liao, Q.; Thumm, U. (My University, 2014)
We compute spectrograms and relative time delays for laser-assisted photoemission by single attosecond extreme ultraviolet pulses from valence band (VB) and 2p core levels (CLs) of a Mg(0001) surface within a quantum-mechanical model. Comparing the time-dependent dispersion of photoelectron (PE) wave packets for VB and CL emission, we find striking differences in their dependence on the (i) electron mean free path (MFP) in the solid, (ii) screening of the streaking laser field, and (iii) chirp of the attosecond pulse. The relative photoemission delay between VB and 2p PEs is shown to be sensitive to the electron MFP and screening of the streaking laser field inside the solid. Our model is able to reproduce a recent attosecond-streaking experiment [S. Neppl et al., Phys. Rev. Lett. 109, 087401 (2012)], which reveals no relative streaking time delay between VB and 2p PEs.